2020
DOI: 10.2196/14861
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Psychological Intervention With a Serious Game to Improve Vitality, Psychological and Physical Condition, and Immune Function in Healthy Male Adults: Randomized Controlled Trial

Abstract: Background Recently, internet-based cognitive behavioral therapy (ICBT) and serious gaming interventions have been suggested to enhance accessibility to interventions and engagement in psychological interventions that aim to promote health outcomes. Few studies, however, have investigated their effectiveness in the context of simulated real-life challenges. Objective We aimed to examine the effectivity of a guided ICBT combined with a serious gaming int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Interestingly, Howells et al [35] reported signi cant improvements for positive affect but not negative affect. In turn, Schakel et al [30] could not identify any signi cant effects, neither for negative nor for positive affect (Table 3).…”
Section: Other Mental Health Outcomesmentioning
confidence: 87%
See 3 more Smart Citations
“…Interestingly, Howells et al [35] reported signi cant improvements for positive affect but not negative affect. In turn, Schakel et al [30] could not identify any signi cant effects, neither for negative nor for positive affect (Table 3).…”
Section: Other Mental Health Outcomesmentioning
confidence: 87%
“…interventions with a duration of more than one month did not show non-signi cant results in mental health-related outcomes [26, 31,32]. However, Schakel et al [30] pointed out signi cant ndings regarding sleep problems and well-being but not quality of life and positive and negative affect, while the intervention duration was six weeks. In contrast, Collins et al [37] indicated within their ve days intervention signi cant improvements in energetic arousal and recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various interventions of serious games have been conducted not only for adolescents [ 31 ] and younger adults [ 32 ] but also for older adults [ 33 - 35 ]. They were applied to older adults in different ways, including video games, using devices such as Nintendo [ 36 , 37 ], and virtual reality serious games [ 38 ].…”
Section: Introductionmentioning
confidence: 99%